Respiratory muscle training : theory and practice - McConnell, Alison, 1961- (Edinburgh ; New York ; Churchill Livingstone/Elsevier, 2013)
Authored by an internationally-acclaimed leading expert, it is an evidence-based resource, built upon current scientific knowledge, as well as clinical experience at the cutting-edge of respiratory training in a wide range of settings. The aim of the book is to give readers: 1) an introduction to respiratory physiology and exercise physiology, as well as training theory; 2) an understanding of how disease affects the respiratory muscles and the mechanics of breathing; 3) an insight into the disease-specific, evidence-based benefits of RMT; 4) advice on the application of RMT as a standalone treatment, and as part of a rehabilitation programme; and finally, 5) guidance on the application of functional training techniques to RMT.
This book includes online access at www.physiobreathe.com, please refer to staff library for the password.
Includes bibliographical references and index.
Keywords: Breathing Exercises; Athletic Performance -- physiology; Respiratory Muscles -- physiology